Smart city workflow patterns for qualitative aggregate information retrieval from distributed public information resources. (2018) - Chu, Wanming
We examine a workflow pattern system for public information from multiple resources. This system aggregates timetable information from bus company, the city information from internet, and the public facilities map of city, to generate geographic data. Multiple query methods are utilised to obtain the target information. For example, one of the search results can be set as the origin or destination of a bus route. Next, the shortest bus route with the minimum number of bus stops between the origin and destination can be found by using the bus routing function. The query results and the shortest bus route are visualised on the embedded map. The detailed search information is shown in the side-bar. This system finds city information and transportation routes. It is helpful for residents and visitors. They can utilise the city public transportation more efficiently for their daily life, business, and travel planning.